Turning residues into valuable compounds: organic waste conversion into odd-chain fatty acids via the carboxylate platform by recombinant oleaginous yeast - Marta de Vicente; Cristina Gonzalez-Fernández; Jean Marc Nicaud; Elia Tomás-Pejó (Microbial Cell Factories)
Abstract Environmental concerns are rising the need to find cost-effective alternatives to fossil oils. In this sense, short-chain fatty acids (SCFAs) are proposed as carbon source for microbial oils production that can be converted into oleochemicals. This investigation took advantage of the outstanding traits of recombinant Yarrowia lipolytica strains to assess the conversion of SCFAs derived from real digestates into odd-chain fatty acids (OCFA). High yeast OCFAs content was aimed by using two engineered strains (Y. lipolytica JMY7780 and JMY7782). Batch and two-step batch fermentations were performed, reaching high lipid content (40.8% w/w) and lipid yield (0.07 g/g) with JMY7782, which overexpresses propionyl-CoA synthase. Fed-batch fermentation with an acetic acid pulse after 24 h was also carried out to promote SCFAs consumption and OCFAs production. In this case, SCFAs consumption rate increased and JMY7782 was able to accumulate up to 60.4% OCFAs of the total lipids produced from food waste-derived carbon sources.